Climate health care: a literature review (Research, Society and Development, 2021)
Objective: To evaluate the assistance provided by the Unified Health System (SUS) to climacteric women through recent literature. Methods: This is an integrative literature review. The Scientific Electronic Library Online (Scielo), Latin American and Caribbean Literature in Health Sciences (LILACS) and the Nursing Database (BDENF) databases were used. The inclusion criteria used were articles published between 2016 and 2021, in Portuguese, original and available in full. Final considerations: Climacteric is represented as the transition from the reproductive to the non-reproductive phase, causing several changes in the body and in the woman's daily life. Therefore, nursing needs to be able to provide specific care for better quality of life and reduced grievances at such stage of the target audience's life.